Comparison of Executive Function and Working Memory among Children with High and Low Levels of Physical Activity - Baniasadi, Tayebeh (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aimed to compare executive functions and working memory among children with high and low levels of physical activity, providing insights into how physical activity influences cognitive development in school-aged children. Methodology: A cross-sectional design was employed, involving 269 children (128 girls) aged 9 to 12 years from regular schools in Tehran. Participants were selected using convenience sampling. Executive functions were assessed using the Behavior Rating Inventory of Executive Function (BRIEF), working memory using the Wechsler Intelligence Scale for Children - Fifth Edition (WISC-V), and physical activity levels using the Physical Activity Questionnaire for Children (PAQ-C). Data were analyzed using SPSS version 27, with descriptive statistics calculated and independent samples t-tests conducted to compare cognitive functions between high and low physical activity groups. Findings: The results indicated significant differences between the two groups. Children with high levels of physical activity demonstrated better executive functions (M = 53.67, SD = 7.89) compared to those with low levels (M = 56.79, SD = 8.22), with a t-value of -3.12 (p = .002). Similarly, working memory scores were higher for children with high levels of physical activity (M = 110.24, SD = 14.78) than for those with low levels (M = 104.72, SD = 15.61), with a t-value of 3.58 (p = .0004). These findings suggest that physical activity is positively associated with better cognitive functions in children. Conclusion: The study provides evidence that higher levels of physical activity are associated with improved executive functions and working memory in children. These findings emphasize the importance of promoting physical activity in schools and communities to enhance cognitive development. Further research using longitudinal designs and objective measures of physical activity is recommended to explore causal relationships and broader implications.